Expression patterns of xenobiotic-metabolizing enzymes in tumor and adjacent normal mucosa tissues among patients with colorectal cancer: the ColoCare Study - Beyerle, Jolantha; Holowatyj, Andreana N.; Haffa, Mariam; Frei, Eva; Gigić, Biljana; Schrotz-King, Petra; Boehm, Juergen; Habermann, Nina; Stiborova, Marie; Scherer, Dominique; Kölsch, Torsten; Skender, Stephanie; et al. (Cancer epidemiology, biomarkers & prevention, 2020)
Background: Xenobiotic-metabolizing enzymes (XME) play a critical role in the activation and detoxification of several carcinogens. However, the role of XMEs in colorectal carcinogenesis is unclear. - Methods: We investigated the expression of XMEs in human colorectal tissues among patients with stage I-IV colorectal cancer (n = 71) from the ColoCare Study. Transcriptomic profiling using paired colorectal tumor and adjacent normal mucosa tissues of XMEs (GSTM1, GSTA1, UGT1A8, UGT1A10, CYP3A4, CYP2C9, GSTP1, and CYP2W1) by RNA microarray was compared using Wilcoxon rank-sum tests. We assessed associations between clinicopathologic, dietary, and lifestyle factors and XME expression with linear regression models. - Results: GSTM1, GSTA1, UGT1A8, UGT1A10, and CYP3A4 were all statistically significantly downregulated in colorectal tumor relative to normal mucosa tissues (all P ≤ 0.03). Women had significantly higher expression of GSTM1 in normal tissues compared with men (β = 0.37, P = 0.02). By tumor site, CYP2C9 expression was lower in normal mucosa among patients with rectal cancer versus colon cancer cases (β = −0.21, P = 0.0005). Smokers demonstrated higher CYP2C9 expression levels in normal mucosa (β = 0.17, P = 0.02) when compared with nonsmokers. Individuals who used NSAIDs had higher GSTP1 tumor expression compared with non-NSAID users (β = 0.17, P = 0.03). Higher consumption of cooked vegetables (>1×/week) was associated with higher CYP3A4 expression in colorectal tumor tissues (β = 0.14, P = 0.007). - Conclusions: XMEs have lower expression in colorectal tumor relative to normal mucosa tissues and may modify colorectal carcinogenesis via associations with clinicopathologic, lifestyle, and dietary factors. - Impact: Better understanding into the role of drug-metabolizing enzymes in colorectal cancer may reveal biological differences that contribute to cancer development, as well as treatment response, leading to clinical implications in colorectal cancer prevention and management.
Published online first November 18, 2019
Gesehen am 22.04.2020